Internet forums following a miscarriage: a place for women in particular pain?. (1st January 2016) - Séjourné, N.; Fagny, J.; Got, F.; Lacroix, P.; Pauchet, C.; Combalbert, L.
Abstract: Objective: Miscarriage is a frequent event, but one which might be particularly difficult to cope with. The main aim of this study was to explore the features of the women using Internet forums following a miscarriage.Methods: A sample of 211 women who experienced miscarriage and who use the Internet completed an online questionnaire. Sociodemographic data were gathered and three scales were completed: the Hospital Anxiety and Depression Scale, the Texas Grief Inventory adjusted to miscarriage and the Dyadic Adjustment Scale.Results: Our results show that these women reported a great amount of pain compared to a more standard sample. Interestingly, our findings show that while women reported wishing to be supported, only a few of them sought such support.Conclusion: Further study focusing on support for women who experience miscarriage must be developed and Internet-based programmes are warranted.